PERAN MEREK, FITUR PRODUK DAN KETERGANTUNGAN PADA PRODUK BERDASARKAN PERBEDAAN GENDER TERHADAP PERILAKU PEMBELIAN (STUDI PADA PENGGUNA SMARTPHONE LOKAL DI BANDUNG) - Munawar, Fansuri (Universitas Pendidikan Indonesia, 2016)
This study examined the influence of the brand, product features and their dependence on the purchasing behavior based on gender differences. Dependent variables in this study were tested by antecedent factors such as social needs, social influence and the convenience of the consumer dependence on smart phones based on gender differences. This study used survey method with simple random sampling was used to collect the questionnaire distributed to 250 students at two universities in Bandung. The data analysis used Stuctural Equation Model (SEM) with AMOS 21 to test the hypothesis. The findings on men and women have differences that can influence the addiction to smart phone, so not all variables could affect reliance on smart phones. The variables that influenced consumer purchase decisions were the product features and the dependent variable, while the brand variable did not affect the local smart phone purchase decision. Keywords: Smart phone, Brand, Product Features, Addiction, Purchase Behavior